PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Fikri -; Retno Andiani Willy Permatasari (STIE Indonesia Malang, 2020)
This study aims to determine the effect of leadership style and work discipline on employee performance at PT. Indosat, Tbk Malang Branch. The analytical method used to test the hypothesis proposed in this study is the method of multiple linear regression. The population in this study were 55 respondents and all of them were determined as research samples.The results of the research prove that partially leadership style factors have a significant influence on employee performance. While simultaneously leadership style and work discipline factors significantly influence employee performance. Keywords: Leadership Style, Work Discipline, Employee Performance